Light as Experience: Rethinking Neo-Assyrian Reliefs in their Architectural Context - Battini, Laura (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2019)
According to recent works by neuroscientists, the brain and memory are largely influenced by biological elements, contingent situations and above all by emotions. The choice of topics and the location of bas-reliefs in Neo-Assyrian palaces seeks to arouse the maximum of emotions and to keep the memory longer, as suggested by neuroscientists. Light plays an important role in emphasising the emotional power of images. The analysis of the light – natural and artificial – in the royal palaces of the 1st mill. BCE highlights also some difficulties in reading bas-reliefs, captions, and inscriptions. It also opens the way to the problem of the ‘babanu-bitanu’ and the audience for whom the bas-reliefs were intended.